JURIDICAL ANALYSIS OF CRIMINAL SANCTIONS FOR NARCOTICS MONEY LAUNDERING - Harry Kurniawan (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
The criminal sanction for laundering money from the crime of narcotics is Article 2 of Law Number 8 of 2010 concerning the prevention and eradication of the crime of money laundering paragraph (1) point 3 concerning narcotics. Implementing the Criminal Sanctions for Money Laundering from Narcotics Crime is still overlapping and separate or simultaneous. This occurs both at the placement, distribution, and collection stages, so handling becomes increasingly difficult and requires systematic and continuous capacity building. Factors constraining Criminal Sanctions for Money Laundering from Narcotics Crime are the Globalization Factor, the Rapid Technological Advancement Factor, and the Very Strict Bank Confidential Provisions Factor of the Country Concerned. Therefore, stricter legal arrangements are needed in enforcing criminal sanctions for money laundering of the proceeds of narcotics crimes and should pay more attention to the principles of simple, fast and low-cost criminal procedural law so that the next stage of the judicial process can be carried out immediately.